Driving style: sex differences and psychological predictors - Astreyko, Natalia S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The theoretical and empirical analysis of sex differences and psychological predictors of driving styles is presented resented. The relevance of identified problem, the relationship of the individual style of activity and driving style are grounded. The driving style is a set of characteristic modes of action of the driver, driving the vehicle, due to a number of personal and situational factors that determine the level of safety (risk of accident) on the road. The study involved 384 drivers. It is established that regardless of the driver’s gender, the dominant driving styles are careful, patient and accident free; preferred ones aggressive, high-velocity and anxious; drivers are less susceptible to risky and dissociative driving styles. Sex differences in the driving style are revealed: risky, angry, high-velocity, anxious, patient and careful. Regression analysis made it possible to calculate psychological predictors of driving styles and to identify the range of factors involved in their formation.
Keywords: driving; driver’s personality; driving style; sex differences; psychological predictors; aggression